The potential of paper pulp bottles with inner protective coatings: a review on sustainable alternatives to petroleum plastic packaging - Hartman, Peter (2023)
Part A: The need to replace petroleum-based plastic vessels for containing liquids has prompted the packaging industry to develop novel materials to store and transport different liquids, such as foods, beverages, colloids, detergents and soaps. This has the effect of reducing pollution and waste emitted from the production, consumption and disposal of plastic. The major issue in using sustainable biomaterials is barrier functionality. Innovative inner protective coatings have been used to overcome the shortcomings of these materials. Many containers use sustainable materials with a plastic-based coating. A novel wax-based coating has been developed by Pulpex to remove plastic entirely. Permeability issues regarding barrier functionality to moisture and homogeneity have yet to be fully resolved and are currently under investigation.